Research on Ecological Compensation Game Model Based on the Willingness Distribution Function - MU Guiling; WANG Jianguo; XIE Yuning; HUANG Wen; QIN Xiaohui (Renmin Zhujiang)
In order to improve the scientificity and rationality of the accounting method of eco-compensation standard,based on the existing accounting methods and game model theory,and combined with the research and analysis results of downstream water receiving areas willingness to pay and water source protection areas willingness to accept,an ecological compensation game model based on the willingness distribution function is proposed.This Model generalizes the willingness density function into an exponential distribution through the research results,and considers both the probability of water source protection area to accept an offer (or charge) and the water receiving area to offer (or accept a charge),which reflects the essence of both the water receiving area and water source protection area to pursue the maximization of their own interests,that is,the higher the offer,the more likely the offer will be accepted.Under the condition that the actual willingness to accept of the water source protection area is known,the water receiving area will raise its offer on the premise of guaranteeing its own interests to reach an agreement as soon as possible.Compared with the original game model,this Model overcomes the shortcoming of the original game model which assumes that the willingness to accept of water source protection area is uniformly distributed,and takes the distribution of willingness to pay of water receiving area into account.The improved game model combines the theoretical basis with the actual investigation,so its result is more reliable.